Criminalizing Rape Within Marriage - Megha (Politikon, 2013)
The paper is an attempt to bring marital rape under the purview of legal discourse in India with substantive equality approach to problematize the existing defined structure of Indian Rape Law. This paper takes up the challenge to create a legal language on the issue of rape within marriage which is till now absent from the legal and social scenario. The equal treatment of women before and under the law within the context of marital rape is critical to ensuring the recognition of women as full citizens, and ensuring their freedom from violence. This paper examines the following questions: how marital rape contributes to and results from women‘s inequality; how the discriminatory roots of the historical- cultural rationales contributes to the exemption of marital rape from the Indian legal system; how the issue of marital rape has been debated in personal-political scenario from the feminist viewpoint; how equality jurisprudence can support the case for the legal treatment of marital rape claims. This paper questions the socio-legal passivity about the suppression of married women; cultivate the knowledge that helps women to generate their own thinking and to apply that in creating the new subjects, to make the women able to express their disagreements about the consent and to make them aware of their active sexuality to provide them bodily integrity. The paper is, thus, an attempt to emphasise the need to transform the prevailing masochistic heterosexual socio- legal matrix. The paper underlines the need to bring the issue of marital rape in the political sphere by bringing this to the purview of Indian law in both formal and substantive manner.